3D carbon nanoframe scaffold-immobilized Ni3FeN nanoparticle electrocatalysts for rechargeable zinc-air batteries' cathodes. (October 2017) - Wang, Qing; Shang, Lu; Shi, Run; Zhang, Xin; Waterhouse, Geoffrey I.N.; Wu, Li-Zhu; Tung, Chen-Ho; Zhang, Tierui
Abstract: Rechargeable zinc-air batteries are attracting enormous attention owing to their extremely high specific energy densities. However, their large scale deployment hinges on the discovery of cheap and efficient electrocatalysts for the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR). Herein, the successful synthesis of a bifunctional hybrid electrocatalyst capable of driving both OER and ORR is reported, comprising Co, N-codoped carbon nanoframes (Co, N-CNF) decorated with 14 nm Ni3 FeN particles, in which the Co, N-codoped carbon nanoframe (Co, N-CNF) with ORR activity was introduced as a scaffold to disperse the precursors and mitigate their further aggregation. The Ni3 FeN/Co, N-CNF hybrid afforded remarkable OER activity (overpotential of 0.27 V, superior to IrO2 ) and excellent ORR performance (half-wave potential of 0.81 V vs RHE, superior to Pt/C), the origins of which can be traced to the inherent activities of the metallic Ni3 FeN nanoparticles and Co, N-CNF support, respectively. Cathodes made from the Ni3 FeN/Co, N-CNF electrocatalyst demonstrated superior efficiency and durability to state-of-the-art Pt/C+IrO2 electrocatalysts in both primary and rechargeable zinc-air batteries, showcasing the versatility of the newly developed Ni3 FeN/Co, N-CNF electrocatalyst system. Graphical abstract: Highlights: A facile strategy to controllable synthesis of a hybrid electrocatalyst comprising 14 nm Ni3 FeN nanoparticles immobilized by 3D carbon nanoframe scaffold (Ni3 FeN/Co, N-CNF) was developed. Ni3 FeN/Co, N-CNF demonstrated outstanding activity and stability for both OER and ORR in solution as well as in rechargeable zinc-air batteries. Synergies realized between the small-sized Ni3 FeN nanoparticles and Co, N-CNF support account for the remarkable performance.